(untitled) (Third Sector Social Economic Review, 2025)
The aim of this study is to reveal the impact of techno-invasion, which arises from the penetration of digital technologies into individuals’private lives, on work-life balance and to examine the mediating role of psychological resilience in this relationship. The main population of the study consists of white-collar employees working in medium and large-scale enterprises operating in Istanbul and Kocaeli provinces. Within the scope of the research, data obtained from 232 employees through a survey were analyzed using the Smart PLS program. The results of the study revealed that as techno-invasion increases, psychological resilience and work-life balance decrease. Additionally, it was found that as psychological resilience increases, work-life balance also increases. The study determined that psychological resilience plays a partial mediating role in the relationship between techno-invasion and work-life balance. This study is one of the pioneering studies that reveals the negative effects of techno-invasion, which refers to the invasive impact of information and communication technologies, on employees’ work-life balance. In today’s business world, where employee experience is prioritized, this finding contributes significantly to the literature on the effects of techno-invasion on psychological resilience. This study deepens the understanding of the impact of information and communication technologies on employees’ lives and emphasizes the importance of psychological resilience. Increasing the psychological resilience of white-collar employees should be considered a critical strategic human resources management practice in mitigating the negative effects of techno-invasion resulting from the intensive use of digital technologies.